Courtroom Language and Article 19(1)(a). Issue 2 (December 2019) - Bhardwaj, Shrutanjaya
Many would agree that the State should try to ensure that the language used in its courtrooms is one that its subjects understand. The question is whether the subjects can claim this as a matter of right—specifically, as part of the right to free speech. Using the philosophical justifications of the freedom of speech, I argue that Article 19(1)(a) of the Indian Constitution assures a right to the litigant to communicate with the court in her own language. Even though the right may be restricted under Article 19(2), or even otherwise if it comes into conflict with another fundamental right, its threshold recognition under Article 19(1)(a) is significant to ensure a disciplined inquiry into the constitutional validity of official courtroom languages.